Chronic peripheral ghrelin injection exerts antifibrotic effects by increasing growth differentiation factor 15 in rat hearts with myocardial fibrosis induced by isoproterenol - Ren, Q; Lin, P; Wang, Q; Zhang, B; Feng, L (Physiological research, 2020)
This study aimed to investigate the anti-fibrotic effects of ghrelin in isoproterenol (ISO)-induced myocardial fibrosis and the underlying mechanism. Sprague-Dawley rats were randomized to control, ISO, and ISO + ghrelin groups. ISO (2 mg/kg per day, subcutaneous) or vehicle was administered once daily for 7 days, then ghrelin (100 microg/kg per day, subcutaneous) was administered once daily for the next 3 weeks. Ghrelin treatment greatly improved the cardiac function of ISO-treated rats. Ghrelin also decreased plasma brain natriuretic peptide level and ratios of heart weight to body weight and left ventricular weight to body weight. Ghrelin significantly reduced myocardial collagen area and hydroxyproline content, accompanied by decreased mRNA levels of collagen type I and III. Furthermore, ghrelin increased plasma level of growth differentiation factor 15 (GDF15) and GDF15 mRNA and protein levels in heart tissues, which were significantly decreased with ISO alone. The phosphorylation of Akt at Ser473 and GSK-3beta at Ser9 was decreased with ISO, and ghrelin significantly reversed the downregulation of p-Akt and p-GSK-3beta. Mediated by GDF15, ghrelin could attenuate ISO-induced myocardial fibrosis via Akt-GSK-3beta signaling.
Keywords: Animals; Heart; ghrelin; Proto-Oncogene Proteins c-akt; Isoproterenol; Fibrosis; růstový diferenciační faktor 15; srdce; kardiomyopatie; Adrenergic beta-Agonists; Rats, Sprague-Dawley; protoonkogenní proteiny c-akt; Male; modely nemocí na zvířatech; potkani Sprague-Dawley; Growth Differentiation Factor 15; agonisté adrenergních beta-receptorů; Disease Models, Animal; Cardiomyopathies; Ghrelin; krysa rodu Rattus; zvířata; mužské pohlaví; Myocardium; fibróza; myokard; Rats; isoprenalin